2015
DOI: 10.1097/sla.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Functional Compromise Reflected by Sarcopenia, Frailty, and Nutritional Depletion Predicts Adverse Postoperative Outcome After Colorectal Cancer Surgery

Abstract: Functional compromise in colorectal cancer surgery is associated with adverse postoperative outcome. Assessment of functional compromise by means of a nutritional questionnaire (Short Nutritional Assessment Questionnaire), a frailty questionnaire (Groningen Frailty Indicator), and sarcopenia measurement (L3 muscle index) can accurately predict postoperative sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
333
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(359 citation statements)
references
References 37 publications
19
333
2
5
Order By: Relevance
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
“…Sarcopenia and myosteatosis have been significantly associated with a range of adverse outcomes including increased rate of post‐operative complications,10, 11, 40, 41, 42 longer length of hospital stay,41, 43 30‐day post‐operative mortality and in‐hospital mortality,44 and dose‐limiting toxicities 5, 6, 7, 8, 45, 46, 47, 48, 49, 50. In addition, the conditions have been demonstrated as independent predictors of reduced overall survival 18, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) imaging has been most frequently used to predict preoperative sarcopenia and investigate the relationship between sarcopenia and postoperative outcomes. However, methods for evaluating total mass of the psoas [14][15][16][17], SM [11][12][13]31], or total volume of the psoas major [15] and cutoff points for sarcopenia differ across studies because of the difficulty in comparing sarcopenic candidates to healthy young adults in term of radiation exposure. How to best characterize sarcopenia remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we examined postoperative complications in more detail. Sarcopenia is not a predictor of anastomotic leakage [31], which is often a fatal SSI after resection of colorectal cancer. We showed that sarcopenia is not associated with SSIs including anastomotic leakage, pancreatic fistula, and intraabdominal abscess, but sarcopenia is associated with non-SSI complications, particularly pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation